Increases in Bdnf DNA Methylation in the Prefrontal Cortex Following Aversive Caregiving Are Reflected in Blood Tissue - Duffy, Hannah B. D.; Roth, Tania L. (Frontiers in Human Neuroscience, 2020)
Child maltreatment not only leads to epigenetic changes, but also increases the risk of related behavioral deficits and mental disorders. These issues presumably are most closely associated with epigenetic changes in the brain, but epigenetic changes in peripheral tissues like blood are often examined instead, due to their accessibility. As such, the reliability of using the peripheral epigenome as a proxy for that of the brain is imperative. Previously, our lab has found aberrant methylation at the Brain-derived neurotrophic factor (Bdnf) gene in the prefrontal cortex of rats following aversive caregiving. The current study examined whether aversive caregiving alters Bdnf DNA methylation in the blood compared to the prefrontal cortex. It was revealed that DNA methylation associated with adversity increased in both tissues. Furthermore, 50% of animals exhibited the same directional changes in both blood and the prefrontal cortex. These findings indicate that group trends in Bdnf methylation between blood and the brain are comparable, but variation exists among individual subjects.